Coronavirus Pandemic: Emergence, Transmission, Preventive Measures and Management - Khinchi, Mahaveer Prasad; Khan, Mohd. Shahid; Saluja, Simranjeet Singh (Asian Journal of Pharmaceutical Research and Development, 2020)
Coronavirus is found in animals and, rarely, can be transmitted from animals to humans and then spread person to person. An occurrence of the coronavirus infection (COVID-19) in China is causing global concern. It came from a seafood and meat market in Wuhan, China, in December 2019. It has since spread to many countries around the world including India. World Health Organization (WHO) declared novel coronavirus eruption a “pandemic” on March 11th, 2020. Patients infected with the COVID-19 virus will experience mild to moderate respiratory illness. Older people and those with underlying medical problems like cardiovascular disease, diabetes, chronic respiratory disease, and cancer are more likely to develop serious illness. Prevent spread of infection by washing hands or using an alcohol based rub frequently and not touching face. This virus transmits primarily through droplets of saliva or discharge from the nose when adiseased person coughs or sneezes, so it’s important to cover face by mask and coughing into a flexed elbow at public places. Currently there are no specific vaccines or treatments for COVID-19. In this review, we summarize recent information about the emergence, tansmission, preventive measures and therapeutic options available now.